2017
DOI: 10.18203/2320-6012.ijrms20174935
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hypertension among young adults in a rural population of North India

Abstract: Background: Most of the studies on hypertension provided the data on older age group. Most of the times, younger population remains unaddressed as they are assumed to be at a lower risk of developing the disease. So, the study on prevalence of hypertension among younger age group and their socio-demographic variables provides the guide for requirements of any intervention. Objective of present study is to estimate the prevalence of Hypertension among young adults in a rural population of central India.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
2
8
0
1
Order By: Relevance
“…12 VivekVerma et al also found that then blood pressure to be positively correlated with age. 11 In the present study, the prevalence of hypertension was found to be 6.59% among males and 4.05% in females. The difference was not found to be statically significant.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…12 VivekVerma et al also found that then blood pressure to be positively correlated with age. 11 In the present study, the prevalence of hypertension was found to be 6.59% among males and 4.05% in females. The difference was not found to be statically significant.…”
Section: Discussionsupporting
confidence: 46%
“…8.5% and 9.2% respectively. 8,11 Taksande et al reported the prevalence of 5.76% among rural school going children (6-16years). 12 The present study reported the prevalence of hypertension of 4.02% among early adolescent age group and 7.21% in mid adolescent age group.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension among younger age group in Malaysia was found to be lower as well where 8.6% of study population 18 to 29 years old and 13.5% of study population 30 to 39 years old had hypertension. This is higher as compared to the developed country such as United States (7.3%) but almost similar to China (8.9% - 14%) and lower compared to India (17.72%) [86, 87, 88].…”
Section: Discussionmentioning
confidence: 98%
“…9 Zafar et al showed overall prevalence 17.7% (males 18.8%, females 15.2%) in Saifai which is comparable to present study. 10 Age is an important non modifiable risk factor for development of hypertension. The prevalence of hypertension was 8.2% in participants less than 25 years, which increased to 44.1% in adults more than 60 years.…”
Section: Discussionmentioning
confidence: 99%